Manajemen Proyek Sistem Informasi Inventaris Pada Toko Apotek - Refi, Novtra; Yahfizham, Yahfizham (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2024)
This research aims to improve the efficiency of warehouse management and sales in pharmacies through transparent and accurate administration. Pharmacies often face challenges in product management and monitoring expiration dates, so complete and accurate data is needed to record purchase and sale transactions. Currently, recording in pharmacies is often done manually, which takes a lot of time and increases the risk of errors and data loss. The research methodology used is qualitative, postpositivist oriented and carried out in a natural environment. This approach aims to understand the context and meaning of the phenomenon under study. Qualitative research is used to hear whether a procedure is right or wrong, as well as to assess the halalness of the process used. With this approach, researchers hope to identify weaknesses in pharmacy administration management and provide more efficient solutions. To overcome this problem, researchers propose implementing a system development process using a waterfall model. The stages in this model include requirements, system design analysis, coding, testing, and implementation. Requirements analysis will help identify the features needed by the pharmacy, while system design will design a solution that meets those needs. Coding will develop the proposed software, which will then be tested to ensure its functionality and security. Ultimately, implementation will ensure the system is implemented well in pharmacies. By implementing this structured and technology-based system, it is hoped that pharmacy management will become more efficient and successful. This system will help pharmacies manage stock, consolidate reach dates, and record transactions automatically and accurately, thereby reducing the risk of errors and increasing productivity. It is hoped that the results of this research can make a real contribution in solving administrative problems often faced by pharmacies.